Ease in Pain and Functional Activities following Caesarean Delivery by Post Natal Exercises (Pilot Study) - Qurat Ul Ain , Fareesa Waqar , Ayesha Bashir (Journal of Islamic International Medical College, 2018)
Objective: To determine effectiveness of post natal exercises to improve incision pain and functional activities in female following cesarean section. Study Design: Experimental, Randomized controlled study design. Place and Duration of Study: The study was conducted in Gynecology and Physiotherapy department of Pakistan Railway Hospital, Rawalpindi from 01 February 2017 to 31 March 2017. Materials and Methods: Twenty women who had undergone caesarian section after spinal or epidural anesthesia were included in the study with informed consent. Patients having multiple births, patients with controlled anesthesia, with general anesthesia, operative complications and fetal abnormalities were excluded. Subjects were randomly allocated in two groups; one receiving post-natal exercise plan and the other receiving routine nursing care. Intervention included Deep breathing exercise, Inter-digital technique, Coughing technique, Ankle pumps, Leg sliding, Pelvic rolling, Abdominal wall setting exercise and Postural education. Exercises were repeated twice a day for three days post cesarean section. Patients were evaluated for general pain intensity, difficulty in functional activities, time of ambulation and analgesic intake on 1 and 2 post-operative day. Results were analyzed on IBM SPSS 20 using independent t test. Results: Mean age of interventional group (n= 10) was 28.10 ± SD 5.30 and 29.60 ± SD 2.54 years for the control group (n = 10). P value for pain was found non - significant (p = 0.152) on 1 post-operative day but showed and significant difference (p = 0.020) on 2 post-operative day indicating better outcomes for exercise group.Significant p values were observed in exercise group for difficulty in performing activities like turning in bed (p =0.001), sitting (p = 0.008), standing (p < 0.001) and walking (p < 0.001). Conclusion: Post Natal exercises improve mobility and reduce pain in females who had undergone caesarian section after spinal or epidural anesthesia.